The Role of Duodenogastroesophageal Reflux in the Progression of Gastroesophageal Reflux Disease: From Esophagitis to Adenocarcinoma - O. A. Storonova; A. V. Paraskevova; A. A. Makushina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present data on the role of bile acids in the progression of Barrett's esophagus (BE) and the development of esophageal dysplasia and adenocarcinoma and to provide a rationale for the use of ursodeoxycholic acid in addition to basic therapy in patients with gastroesophageal reflux disease (GERD).Key points. The prevalence of GERD in the world is 13.98 %. In the absence of the necessary treatment or non-compliance with the recommended regimens and duration of drug use, complications of GERD develop such as stricture, bleeding, BE, which, in turn, is a risk factor for the development of esophageal adenocarcinoma (EAC). The basic therapy for GERD is proton pump inhibitors (PPIs), but up to 40 % of patients do not fully respond to PPI monotherapy, which indicates the need to consider, among the factors in the pathogenesis of GERD, the persistence of weakly acidic and weakly alkaline refluxes, the presence of which can be diagnosed by performing 24-hour impedance-pH monitoring. It has been proven that refluxate is predominantly acidic in nature in 50 % of patients with GERD, acidic with a bile component in 39.7 %, and 10.3 % of patients have bile reflux. The weaklly alkaline nature of reflux, due to the presence of duodenal contents, significantly increases the incidence of intestinal metaplasia with dysplasia and EAC compared to acidic pH values. Therefore, stopping duodenal reflux may be an important step in preventing the development of EAC. Among the components of duodenal contents that have a damaging effect on the mucous membrane of the esophagus, the role of bile acids has been most studied. The presence of hydrophobic bile acids, namely deoxycholic acid (DCA), is associated with oxidative DNA damage in lesions of intestinal-type columnar cell metaplasia. Ursodeoxycholic acid (UDCA), a hydrophilic bile acid, is a natural competitive inhibitor of DCA and prevents DNA damage and nuclear factor-κB (NF-κB) activation caused by toxic bile acids in BE epithelial cells. The cytoprotective effect of UDCA, aimed at preventing DNA damage and increasing the reparative capacity of cells in the metaplastic epithelium of the BE, allows us to consider this drug as a means of chemoprophylaxis in patients diagnosed with GERD.Conclusion. The addition of UDCA drugs to the basic therapy is pathogenetically justified in patients with GERD in the presence of duodenogastroesophageal reflux. Prescribing complex therapy will reduce the incidence of esophagitis, progression of BE with the development of dysplasia and adenocarcinoma caused by exposure to bile acids.